PO 95 - AIRWAY APPROACH TO AN UNEXPECTED GIGANT VALLECULAR CYST IN AN INFANT - Pinto, Ana Marta; Rocha, Valter; Costa, Catarina; Rui Loução, Maria (Journal of the Portuguese Society of Anesthesiology, 2023)
x